Optimization Of Solar Drying Parameters for Turmeric and Papaya Leaves: Effects on Nutritional and Bioactive Compound Retention - Narendra Dnyanoba Dudhmal; Prashant Laximan Pandit; Nilesh Diwakar (International Journal of Electrical Power and Machine Systems, 2025)
This study focuses on the optimization of solar drying parameters for turmeric and papaya leaves, based on their impact on retention of nutritional and bioactive compounds. One of the most crucial postharvest procedures is solar drying as it decreases the moisture content in plant materials, thereby increasing shelf life and preserving quality. This study considers traditional methods as open sun drying (OSD) and advanced solar dry techniques, including Hybrid Indirect Passive (HIP) and other innovative dryers. It stresses the role of drying conditions in retaining bioactive compounds like curcumin and flavonoids, which are very important for food and pharmaceutical applications. The study compares solar drying with conventional methods, emphasizing energy efficiency, environmental impact, and preservation of nutritional properties. The aim of the study is recommending sustainable and efficient drying technologies that can be applied in industrial practices.
Keywords: Bioactive compounds; Solar drying; drying optimization; nutritional retention; papaya leaves; turmeric